O indivíduo urbano: cotidiano, resistência e políticas públicas em pequenas cidades do oeste de santa catarina - Bavaresco, Paulo Ricardo (Universidade do Vale do Rio dos Sinos, 2010)
In this thesis, we discuss the daily life of the urban individual and the trajectory of public policies in the small towns of the West of Santa Catarina, to understand how these urban public policies are introduced from the resistance and strategies used by individuals in everyday life. The Literature reviews supported understanding and comprehension of the relationship between public policy and everyday life of the urban individual. Based on primary sources like oral history of the inhabitants of the cities under study, we observed the daily life and the strategies used to achieve certain individual or collective goals. In this aspect, we assume that the individual is a being of projects, and to achieve certain goals he establishes strategies for this purpose. The projective dimension is motivational and among several factors that surround it, the main ones are values, feelings, or even adventures. The dichotomy between public and private is, by several times, expressed in a system of spontaneous perceptions as if it were an organizing contract of everyday life. Thus, through sociological analysis, we highlight the public / private dichotomy and ambiguity in its multiple criteria analysis. We observed that the strategies and the daily survival resistance of the urban individual and the promotion of public policies is the attempt to give meaning to life itself. This autonomy of creating and organizing strategies to achieve a certain purpose, lies in its inner motivation and is the very freedom of being. That freedom that makes him individualizing is also caused by the process of technological globalization process, which increases the limits and possibilities of man. In this scenario, cities are being world market driven and shaped from global cultural values. Thus, small towns are placed in the same windows that medium and large cities, namely, the policies adopted in small towns are the same policies of the large urban centers. This demonstrates that in studies about cities, the statistical analysis of medium and large can be extended to small towns. Therefore, when differentiating small and large cities, it is necessary to observe the social and cultural relations in the living space as well as the interference with the individual rationality. Only then you can note the development of objective culture in relation to subjective culture.
Keywords: Indivíduo urbano; Cotidiano; Políticas públicas; Urban individual; Everyday life; Public policies; ACCNPQ::Ciências Humanas::Sociologia